Analisis Lean Manufacturing Untuk Meningkatkan Efisiensi Produksi Pada Industri Manufaktur Dengan Metode Studi Literatur - Dikri Zamzam Ramadhan; Rifqi Susanto; Zhaky Raditya Wardhana; Yudi Prastyo (GLOBAL SCIENTS PUBLISHER, 2026)
The manufacturing industry faces challenges in increasing production efficiency due to the high level of waste, such as waiting time, overproduction, and product defects. This study aims to analyze the application of lean manufacturing in improving production efficiency in the manufacturing industry. The method used is a literature study by reviewing various scientific journals, books, and relevant sources that discuss the concept of lean manufacturing and its implementation. The results of the analysis show that the application of lean manufacturing with various tools such as Value Stream Mapping (VSM), Waste Assessment Model (WAM), and Value Stream Analysis Tools (VALSAT) can significantly increase production efficiency. Data from several studies show an increase in production efficiency from 67.06% to 86.52%, an increase in process cycle efficiency of 7.61% (from 48.85% to 56.56%), and a decrease in manufacturing lead time from 14,415 seconds to 9,875 seconds, accompanied by an increase in process cycle efficiency from 30.35% to 44.30%. The results of the discussion indicate that lean manufacturing is effective in identifying and eliminating non-value-added activities so that the production process becomes faster, more efficient, and more productive. In conclusion, the implementation of lean manufacturing is an effective and strategic approach to increasing the efficiency and productivity of the manufacturing industry through waste reduction and continuous improvement.